PRODUCT QUALITY AND PROMOTION OF CONSUMER SATISFACTION THROUGH PRICE AS AN INTERVENING VARIABLE - Hadmar, Ambo Sakka; Andi Ansur Pranata (Jurnal Ekonomi, 2022)
The test has the intention to understand the effect of Product Quality and Promotion on Consumer Satisfaction through Price as an Intervening variable in Kenari Coffee. The research population is 30 people Kenari Coffee consumers with data collection techniques in the form of distributing questionnaires. Data testing was carried out using the SEM-PLS..on.software.SmartPLS.3.0 method. The results showed that product quality had a significant effect on consumer satisfaction in walnut coffee without going through the price variable as an intervening variable. Promotion has no significant effect on consumer satisfaction at walnut coffee without going through the price variable as an intervening variable and promotion has a significant effect on consumer satisfaction at walnut coffee through the price variable as an intervening variable.